Microwave Assisted Glycerolysis Of Neem Oil - Isabela Celina del Mundo; John Michael Cavarlez; Anna Monica Pe; Susan Roces (ASEAN Journal of Chemical Engineering, 2018)
Biodiesel is considered as a viable alternative to diesel fuels since it is renewable and eco-friendly. Edible oils account for majority of feedstock oils used in biodiesel production since their free fatty acids (FFA) levels are below 1%. However, these oils are expensive and compete with food demand. Low cost feedstock oils may be used but they must undergo a pre-treatment process (glycerolysis) to reduce their FFA content to less than 1%. Conventional glycerolysis requires long reaction times so microwave irradiation is used to speed up the process. Neem oil with an initial %FFA of 1.138% was used to determine the effect of microwave irradiation on different factors that would affect the FFA reduction. The following factors are investigated: reaction time (5 and 9 minutes), reaction temperature (100°C and 120°C), oil to glycerol molar ratio (1:1 and 1:2) and sulfuric acid catalyst concentration or loading (2% and 4.5%). This study reports that reaction temperature was the only significant factor on FFA reduction. A higher temperature resulted in a higher FFA reduction. The optimum factors achieved are: oil to glycerol molar ratio of 1:1, a catalyst loading of 2%, a time of 5.58 minutes and a reaction temperature of 120°C resulting in a 91.81% FFA reduction